Proyecto hidrologico río chimbo - Orozco Coello, Danny (2010)
Our country has had electric energy rationing problems, which owes to different factors; one of them is the high price of the energy, one of the highest of the region, product of the dependence on thermal generation. Another factor is the dependence on our biggest electrical generation project, Paute - Molino, which delivers a large percentage of the electric energy of our country. Despite this, in the drought months its installed capacity is missed because of the lack of water resource, it is then when energy rationing occurs. To face these problems it is necessary to boost hydroelectric projects of the basin of Guayas, which are capable of providing energy during these drought months and replacing thermoelectric energy during the rest of the year, obtaining with this to low the energy price. Particularly, this project analyzes the possibility of developing the hydroelectric plants one after another, in Chimbo River, denominated”River Chimbo Hydrologic Project”.